Filling the gap: investigating the interpretability of the Recap of atopic eczema questionnaire - Ofenloch, Robert (British journal of dermatology, 2023)
According to the Global Burden of Disease Study, atopic dermatitis (AD) ranks number 15 among all nonfatal diseases and has the highest disease burden among skin diseases.1 AD is a chronically relapsing inflammatory skin condition characterized by dry, itchy and inflamed skin, and is associated with emotional and behavioural problems.2 Therefore, it is important to assess disease control over time in patients with AD, both in clinical trials addressing new treatments for AD and in clinical practice. It can support clinicians in identifying environmental or emotional factors triggering the disease.
Veröffentlicht: 09. August 2023
Gesehen am 16.10.2023